Study of the radio and optical properties of Active Galactic Nuclei - Abrahamyan, H. V.
The investigation of the physical properties of active galactic nuclei is one of the most important tasks of astronomy. Until now, the properties of AGN have not been fully studied. Therefore, we have studied a number of important properties of AGN. For example, one of the main properties of AGN is the variability. We have studied samples of AGN derived by different methods. For these sources, we have identified some properties of activity for the radio and optical ranges. These properties give us some insight into the active galaxies.
Keywords: Astronomy